NOTES ON HENRIK IBSEN SCHOLARSHIP TODAY: POTENTIALS AND CHALLENGES IN COMBINING HISTORIOGRAPHICAL METHODS, DIGITAL HUMANITIES, AND THEATRE/LITERARY STUDIES - DRUȚĂ, Gianina (Studia Universitatis Babeș-Bolyai Philologia, 2020)
Notes on Henrik Ibsen Scholarship Today: Potentials and challenges in Combining Historiographical Methods, Digital Humanities and Theatre/Literary Studies. This paper explores the potentials and challenges encountered in the recent Henrik Ibsen scholarship emerging from the methodological combination of historiographical methods, digital humanities, and theatre/literary studies. In the first part, the article discusses the methodological intercrossings through examples from the Ibsen field. For this purpose, it takes theatre historiography, theatre/literary studies and digital humanities as different yet interconnected methodological portals to access the Ibsen world. In the second part, the article takes the methodological discussion further, by bringing into light the main four steps generally taken by researchers when working with this methodological combination. In this account, the IbsenStage Database[2] is the most powerful example of a research tool at crossroads between historiography, digital humanities, theatre and literature in the Ibsen field. Finally, the article concludes that the potentials and challenges in combining historiographical methods, digital humanities and theatre/literary studies revealed in the examples demonstrate the inescapable interconnectedness of quantitative and qualitative approaches not only in the Ibsen research, but also in the humanities in general. REZUMAT. Note asupra cercetării ibseniene recente: Oportunități și provocări în combinarea metodelor istoriografice, umanioarelor digitale și a studiilor literare/teatrale. Acest articol explorează oportunitățile și provocările din cercetarea ibseniană recentă care a valorificat combinația metodologică dintre metodele istoriografice, umanioarele digitale și studiile teatrale/literare. În prima parte, articolul discută aceste intersecții metodologice prin exemple din studii care abordează opera și receptarea lui Henrik Ibsen. Din această perspectivă, articolul consideră istoriografia teatrală, studiile teatrale și literare, precum și umanioarele digitale ca portale metodologice diferite, dar interconectate prin care putem accesa universul ibsenian. În a doua parte, articolul duce discuția metodologică și mai departe, punând în lumină cei mai importanți patru pași urmați de cercetători atunci când aleg această combinație metodologică. În acest context, baza de date IbsenStage este exemplul cel mai puternic de instrument de cercetare la intersecția dintre istoriografie, umanioare digitale, teatru și literatură în domeniul studiilor ibseniene. În cele din urmă, articolul demonstrează prin exemplele prezentate privind oportunitățile și provocările care apar atunci când combinăm metode istoriografice și umanioarele digitale cu studiile literare/ teatrale că studiile cantitative și calitate sunt interconectate nu doar în cercetarea ibseniană, ci și în domeniul umanioarelor în general. Cuvinte cheie: Henrik Ibsen, IbsenStage, istoriografie teatrală, umanioare digitale, studii teatrale, studii literare, oportunități, provocări, metodologie